Empowering Machine Learning for Virtual And Augmented Reality in Education: A Systematic Review Of Current Trends and Techniques - Fuad Manna Fataftah; Siti Hazyanti Mohd Hashim; Mohammed Wedyan (Universitas Airlangga, 2026)
Background: Machine learning (ML) integrated with virtual reality (VR) and augmented reality (AR) is also becoming widespread in education, especially in the STEM and medicine fields. The technologies have proved to be promising in improving learners’ engagement, learning capabilities, and practical skills with the help of immersive experiences. However, the overall picture of the effects of ML-based VR and AR devices on pedagogical outcomes has not been fully studied. Objective: This study aimed to conduct a systematic literature review to understand how ML-integrated VR and AR technologies are used in the educational process, how effective they are in enhancing learning outcomes,and the challenges hindering their implementation. Methods: A Preferred Reporting Items for Meta-analysis (PRISMA)-based systematic literature review was conducted. Database searches identified 210 records. In the final qualitative synthesis, 22 peer-reviewed articles were included in the screening and eligibility test. The themes used in the analysis of the studies included trends in publications, uses of technologies, effects of learning, user experience, theory of use, implementation issues, and perspectives on future research. Results: VR and AR led to improvements in conceptual understanding, problem-solving, and engagement of learners. ML applications include adaptive learning and other applications in biometric feedback systems and intelligent tutoring. However, the main obstacles were high prices, technical nature, and lack of transfer of skills. A small sample size and context-specific findings were reported in most of the studies. Conclusion: The review established the pedagogical promise of integrating ML-VR and AR but emphasized the need for scaled, all-inclusive, and cross-disciplinary applications. The research should be further enhanced in the future with the longitudinal effects of AI, the model of AI personalization, and learner types to enhance the learning potential. Keywords: Machine Learning, Virtual Reality, Augmented Reality, Education Technology, Immersive Learning, Systematic Review